Les genres récrits n° 3 - Daniel Elmiger (Glad!)
What does the word “gender" mean, in language? It is used, among other things, to designate grammatical genders as well as gender identities. What can we do when such an identity does not correspond to a binary choice (such as “woman” or “man”) or when a person undertakes a transition? How does this translate in terms of language? In this column, different processes are presented and discussed.